Studies on growth, yield and soil micrflora of tomato under various organic nutrient management practices - Divya M.; Pradeep S.; Srikanth C.D. (Annals of Agricultural Research, 2023)
A field experiment was conducted to evaluate the growth and yield of tomato under different organic nutrient management practices during kharif 2017-18 at Organic Farming Research Centre, University of Agricultural and Horticultural Sciences, Shimoga. Tomato variety 'Arka Rakshak' used under different doses of FYM and vermicompost. Results of the study revealed that, application of recommended FYM along with vermicompost at 100% N equivalent basis resulted in enhanced plant height, number of leaves, clusters (7.6), fruits (14.80), fruit weight (51.20 g) and fruit yield (693g/plant and 15.89 t/ha) over alone application or in combination of FYM and vermicompost. Correspondingly, the same treatment recorded highest soil microbial populations such as bacteria, fungi, actinomycetes, P-solubilizers and nitrogen fixers over others. Interestingly, the application of recommended FYM along with 50% N equivalent of vermicompost also influenced significantly on growth and yield of tomato.